OPTIMISASI PARAMETRIK FASAD BILAH HORIZONTAL TERHADAP PENCAHAYAAN ALAMI DENGAN METRIK USEFUL DAYLIGHT ILLUMINANCE (UDI) DI KOTA LHOKSEUMAWE - Atthaillah, Atthaillah; Mangkuto, Rizki Armanto (Nature: National Academic Journal of Architecture, 2020)
Abstrak_ Studi ini melakukan optimasi pengaruh rotasi (α) dan lebar bilah (l) pada fasad bilah horizontal untuk pencahayaan alami yang optimal di Kota Lhokseumawe. Sebuah ruang belajar sekolah dasar hipotetik tanpa konteks dimodelkan secara komputasional kemudian diuji dengan metrik UDI. Metode optimasi dengan Genetic Algorithm (GA) dengan Galapagos digunakan untuk mendapatkan solusi-solusi rotasi dan lebar bilah yang optimal terhadap pencahayaan alami. Mesin simulasi Radiance dan Daysim digunakan yang dihubungkan dengan perangkat permodelan parametrik dengan aplikasi Rhinoceros dan Grasshopper melalui plugins Ladybug Tools. Optimasi dilakukan untuk mendapatkan nilai UDIo.avg (100-2000 Lux) paling maksimal. Hasil menunjukkan bahwa terdapat pengaruh rotasi dan lebar bilah yang berbeda-beda untuk setiap orientasi di Kota Lhokseumawe. Ada dua orientasi yang dapat dirasionalkan hasil optimasi dari GA yaitu Utara dengan nilai α=90 dengan beberapa nilai lebar bilah yaitu l=0,20m, l=0,22m, l=0,43 dan l=0,45m mendapatkan nilai UDIo.avg=100%, serta hadapan Timur dengan satu kombinasi yaitu α=-80, l=0,30m dengan UDIo.avg=99,29%. Sementara, sisi Selatan dan Barat direkomendasi untuk memilih kombinasi solusi-solusi optimal yang sangat variatif oleh GA yang disajikan pada penelitian ini. Lebih lanjut, hadapan Utara dan Selatan mendapatkan solusi optimal dengan diferensiasi sudut yang kecil terhadap sudut 90 derajat dari bilah horizontal. Solusi-solusi optimal yang variatif dari sudut rotasi dan lebar bilah yang didapatkan dengan metode GA dapat menguntungkan untuk menciptakan desain fasad yang terlihat tidak seragam untuk setiap orientasi atau bahkan pada satu orientasi. Kata kunci : Optimisasi; Pencahayaan Alami; Desain Fasad; Bilah Horirizontal; Useful Daylight Illuminance. Abstract_ This study examined the effects of optimizing rotation (α) and width (l) of the horizontal blades for optimal daylighting in Lhokseumawe. A hypothetical elementary classroom, without any context, was computationally designed and examined using UDI metric. Optimization Genetic Algorithm (GA) method with Galapagos were used to obtain the rotation solution and optimal daylighting. Moreover, Radiance and Daysim simulation engines connected to parametric platform of Rhinoceros and Grasshopper using Ladybug Tools as mediating tools were administered for the analysis. The optimization was aimed at maximum UDIo.avg (100-2000 Lux). Result revealed rotation and width of the horizontal blades contributed differently to every orientation in Lhokseumawe. Two orientations were succeeded to be rationalized based on GA opmization results, first, North showed α=90 and some blades’ width of l=0,20m, l=0,22m, l=0,43 and l=0,45m resulted in UDIo.avg=100%. Second, East orientation for the combination of α=-80, l=0,30m resulted in UDIo.avg=99,29%. Further, South and West to maintained solutions from the GA optimization results as presented in this paper. In addition, North and South sides suggested a small differentiation for its rotation from full horizontal blades, which was 90 degrees. Various optimum design solutions, for rotation and width of the blades, from the GA benefitted to create non-uniform façade design for different or even at the similar orientation. Keywords : Optimization; Daylighting; Façade Design; Horizontal Blades; Useful Daylight Illuminance. This study conduct an optimization for rotation (α) and width (l) of horizontal blades for an optimal daylighting in Lhokseumawe. A hypothetical classroom for elementary school, without any context, was computationally modeled and examined using UDI metric. Optimization utilizing Genetic Algorithm (GA) using Galapagos was a tool to explore for rotational and width of the blades for an optimal daylighting inside the room. Further, Radiance and Daysim were main simulation engines for daylighting through parametric platform of Rhinoceros and Grasshopper using Ladybug Tools as mediating tools to connect to the daylighting simulation engines. The optimization was aimed at maximum UDIo.avg (100-2000 Lux). Result revealed rotation and width of the horizontal blades contributed differently to every orientation in Lhokseumawe. Two orientations were succeeded to be rationalized based on GA opmization results, first, North showed α=90 and some blades’ width of l=0,20m, l=0,22m, l=0,43 and l=0,45m resulted in UDIo.avg=100%. Second, East orientation for the combination of α=-80, l=0,30m resulted in UDIo.avg=99,29%. Further, South and West to maintained solutions from the GA optimization results as presented in this paper. In addition, North and South sides suggested a small differentiation for its rotation from full horizontal blades, which was 90 degrees. Various optimum design solutions, for rotation and width of the blades, from the GA benefitted to create non-uniform façade design for different or even at the similar orientation.